In-plant alliances can mitigate economic crisis impacts - Lutz Bellmann; Werner Widuckel (IZA World of Labor, 2022)
In-plant alliances are plant-specific deviations from sectoral collective agreements related to wages and working time that are intended to hold down labor costs. These agreements enable firm-level reorganizations to respond to an imminent economic crisis or to improve competitiveness. They also encourage social partners to take greater responsibility for employment issues. Both unions and works councils agree to such contracts because they see them as helpful in avoiding severe employment losses. Thus, these alliances substantially unburden public employment policy.
Keywords: J23; J52; 330; in-plant alliances; decentralization of wage setting; global economic crisis; employment effects